Term breech presentation—Intended cesarean section versus intended vaginal delivery—A systematic review and meta‐analysis - Julia Wängberg Nordborg; Therese Svanberg; Annika Strandell; Ylva Carlsson (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Three per cent of all infants are born in breech presentation, still the preferred way to deliver them remains controversial. The objective of this systematic review was to assess the safety for the mother and child depending on intended mode of delivery when the baby is in breech position at term. Material and Methods The population (P) was pregnant women with a child in breech presentation, from gestational week 34+0. The intervention (I) was the intention to deliver by cesarean section, the comparison (C) was the intention to deliver vaginally. Outcomes (O) were perinatal mortality, perinatal morbidity, maternal mortality, maternal morbidity, conversion of delivery mode, and the mother's experience. Systematic literature searches were performed. We included randomized trials, cohort studies with more than 500 women/group and case series for more than 15 000 women published between 1990 and October 2021, written in English or the Nordic languages. The certainty of evidence was assessed using the GRADE approach and data were pooled in meta‐analyses. PROSPERO registration number: CRD42020209546. Results Thirty‐two articles were included (with 530 604 women). The certainty of evidence was moderate or low because the study designs were mostly retrospective cohort studies. The only randomized trial showed reduced risk of perinatal mortality for planned cesarean section, risk ratio (RR) 0.27 (95% confidence interval [CI] 0.08–0.97, 2078 women, low certainty of evidence), stillbirths excluded. A meta‐analysis of cohort studies resulted in a similar estimate, RR 0.36 (95% CI 0.25–0.51, 21 studies, 388 714 women, low certainty of evidence). We also found reduced risk for outcomes representing perinatal morbidity 0–28 days: 5‐min Apgar score less than 7 in one randomized controlled trial: RR 0.27 (95% CI 0.12–0.58, 2033 women, moderate certainty of evidence), and in a meta‐analysis: RR 0.1 (95% CI 0.14–0.26, 18 studies, 217 024 women, moderate certainty of evidence); APGAR score less than 4 at 5 min: RR 0.39 (95% CI 0.19–0.81, five studies, 44 498 women, low certainty of evidence); and pH less than 7.0: RR 0.23 (95% CI 0.12–0.43, four studies, 13 440 women, low certainty of evidence). Outcomes for the mother were similar in the groups except for reduced risk for experience of urinary incontinence in the group of planned cesarean section: RR 0.62 (95% CI 0.41–0.93, one study, 1940 women, low certainty of evidence). The conversion rate from planned vaginal delivery to emergency cesarean section ranged from 16% to 51% (median 41.8%, 10 studies, 50 763 women, moderate certainty of evidence). Conclusions Intended cesarean section may reduce the risk of perinatal mortality and perinatal as well as some maternal morbidity compared with intended vaginal delivery. It is uncertain whether there is any difference in maternal mortality. The conversion rate from intended vaginal delivery to emergency cesarean section is high.